2016
DOI: 10.1186/s12862-016-0818-6
|View full text |Cite
|
Sign up to set email alerts
|

Resurrecting ancestral structural dynamics of an antiviral immune receptor: adaptive binding pocket reorganization repeatedly shifts RNA preference

Abstract: BackgroundAlthough resurrecting ancestral proteins is a powerful tool for understanding the molecular-functional evolution of gene families, nearly all studies have examined proteins functioning in relatively stable biological processes. The extent to which more dynamic systems obey the same ‘rules’ governing stable processes is unclear. Here we present the first detailed investigation of the functional evolution of the RIG-like receptors (RLRs), a family of innate immune receptors that detect viral RNA in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 150 publications
0
5
0
Order By: Relevance
“…Characterizing how protein function evolves over long timespans can inform our understanding of the structural basis for functional differentiation and impact the development of evolutionary theory ( Lunzer et al 2005 ; Dean and Thornton 2007 ; Bridgham et al 2008 ; Hobbs et al 2012 ). Mechanistic studies of functional evolution have demonstrated how historical changes in protein sequence can alter molecular structure, resulting in qualitative and quantitative shifts in ligand preference ( Bridgham et al 2009 , 2014 ; Kratzer et al 2014 ; Pugh et al 2016 ). However, deriving generalizable information about the evolution of sequence-structure-function requires characterizing a large number of diverse protein families interacting with a variety of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing how protein function evolves over long timespans can inform our understanding of the structural basis for functional differentiation and impact the development of evolutionary theory ( Lunzer et al 2005 ; Dean and Thornton 2007 ; Bridgham et al 2008 ; Hobbs et al 2012 ). Mechanistic studies of functional evolution have demonstrated how historical changes in protein sequence can alter molecular structure, resulting in qualitative and quantitative shifts in ligand preference ( Bridgham et al 2009 , 2014 ; Kratzer et al 2014 ; Pugh et al 2016 ). However, deriving generalizable information about the evolution of sequence-structure-function requires characterizing a large number of diverse protein families interacting with a variety of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IFIH1/DDX58 is the primary cytoplasmic sensor for the intracellular detection of viral pathogen-associated molecular patterns of viral RNA ( 29 ). It is an important component in the formation of cytoplasmic RNA-binding protein complement, which contributes to innate antiviral immunity ( 30 ). IFIH1/DDX58 expression in epithelia of the upper airway is higher in children than in adults, resulting in stronger early innate antiviral immunity to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in children ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…2017 ), RIG-like receptor ( Mukherjee et al. 2014 ; Pugh et al. 2016 ), and CARD ( Korithoski et al.…”
Section: Methodsmentioning
confidence: 99%